Pure inorganic water-based zinc-aluminum coating as well as preparation method and application thereof

By using modified ultrafine scale zinc-aluminum powder and modified inorganic salt composite agent in anticorrosion coatings, the existing anticorrosion technology is not environmentally friendly and weak adhesion is solved, and the coating is high wear resistance, high temperature resistance and long service life are achieved, ensuring the safety of the environment and use.

CN119875406AActive Publication Date: 2025-04-25HUNAN BONENG NEW MATERIALS CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510188321.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-20
Publication Date
2025-04-25
Estimated Expiration
2045-02-20

AI Technical Summary

Technical Problem

The existing anti-corrosion technology is not environmentally friendly enough, has weak adhesion, complex construction technology, and has a short service life of the paint.

Method used

The pure inorganic water-based zinc-aluminum coating is used to improve the corrosion resistance, wear resistance, chemical corrosion resistance and high temperature resistance of the coating by combining modified ultrafine flaky zinc-aluminum powder and modified inorganic salt composite agent.

Benefits of technology

It achieves good adhesion, long service life, environmental protection and simplicity of construction of the coating, avoids the emission of organic volatiles, and ensures environmental safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005279214260000061
    Figure BDA0005279214260000061
Patent Text Reader

Abstract

The invention relates to the technical field of coatings, in particular to a pure inorganic water-based zinc-aluminum coating as well as a preparation method and application thereof. The pure inorganic water-based zinc-aluminum coating comprises modified superfine flaky zinc-aluminum powder and a modified inorganic salt compound complexing agent, wherein the modified superfine flaky zinc-aluminum powder comprises flaky zinc-aluminum powder, titanium dioxide, fumed silica and boron nitride; the modified inorganic salt compound complexing agent comprises silicate, a stabilizer, a water repellent and distilled water; and uniformly mixing the modified superfine flaky zinc-aluminum powder and the modified inorganic salt compound complexing agent according to the weight ratio of 1: 2.4 to obtain the coating. The problems that an anti-corrosion technology is not environment-friendly enough, the adhesive force is weak, the construction process is complex, and the service life of the coating is short are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coatings, in particular to a pure inorganic water-based zinc-aluminum coating, a preparation method and application thereof. Background Art

[0002] The most common anti-corrosion technologies at present are cold-dip galvanizing, hot-dip galvanizing, epoxy zinc-rich and Dacromet coating.

[0003] Among them, cold galvanizing: the zinc coating is only 1 to 3μm, and the product manufacturing process is not environmentally friendly, the product is not repairable, and the damage to the anti-corrosion layer after welding cannot be repaired.

[0004] Hot-dip galvanizing: The thickness of the metal surface coating is difficult to control, and the metal is prone to hydrogen embrittlement. The metal dipping process is not environmentally friendly and the product is not repairable.

[0005] Epoxy zinc-rich coating: It is not environmentally friendly when applied on the construction site. The salt spray resistance test lasts for 80 to 120 hours. It is easy to corrode and fall off in coastal environments. The construction process may cause secondary environmental pollution and it is not resistant to high temperatures.

[0006] Dacromet coating: The coating process of Dacromet is relatively complicated. The theoretical sintering temperature is 320°C, the actual temperature is 370 degrees, and the baking time is 40 to 60 minutes. Due to process limitations, it is currently mainly used for small workpiece processing in automobile manufacturing and other fields, and its application field is relatively narrow.

[0007] In summary, there is no mature pure inorganic water-based anti-corrosion coating available for engineering construction in the market. The volatiles of organic coatings will cause secondary pollution to the environment and cause certain harm to people who come into contact with the coatings. In addition, the water-based coatings currently used in the market actually also contain organic components. Organic volatiles will be produced during the coating process, causing secondary pollution to the environment. More importantly, these water-based coatings are limited by their mechanism of action, have insufficient bonding strength with the metal surface, poor thickness resistance, and the paint film is easy to fall off, resulting in a short service life of the coatings. Summary of the invention

[0008] In order to solve the problems in the related art, the present invention provides a pure inorganic water-based zinc-aluminum coating, a preparation method and an application, which solves the problems that the anti-corrosion technology is not environmentally friendly, the adhesion is weak, the construction process is complicated, and the service life of the coating is short.

[0009] In order to solve the above problems, the following technical solutions are provided:

[0010] The pure inorganic water-based zinc-aluminum coating of the present invention is characterized by comprising modified ultrafine flaky zinc-aluminum powder and a modified inorganic salt complexing agent.

[0011] The modified ultrafine flaky zinc-aluminum powder includes the following raw materials in parts by weight:

[0012] The weight proportion of the flaky zinc-aluminum powder is 25 to 35 parts, the weight proportion of titanium dioxide is 0.5 to 2 parts, the weight proportion of fumed silicon dioxide is 0.1 to 0.5 parts, and the weight proportion of boron nitride is 0.1 to 0.5 parts;

[0013] The modified inorganic salt complexing agent includes the following raw materials in parts by weight:

[0014] The weight proportion of the silicate is 40-50 parts, the weight proportion of the stabilizer is 20-30 parts, the weight proportion of the hydrophobic agent is 0.1-1 part, and the weight proportion of the distilled water is 0.1-1 part.

[0015] Through the above scheme, the present invention reasonably matches the raw material components with different functions to achieve the best synergistic effect between the different raw material components. The addition of flaky zinc-aluminum powder is used to improve the corrosion resistance of the coating, and is also beneficial to improving the wear resistance, chemical corrosion resistance and high temperature resistance of the coating; by adding titanium dioxide, the hardness of the coating and the dispersibility of the flaky zinc-aluminum powder are increased; by adding fumed silica, the hardness, wear resistance and stability of the coating can be significantly improved, and the service life of the coating is extended. At the same time, the coating has good fluidity during construction, and the thickness and uniformity of the coating are guaranteed; by adding boron nitride, boron nitride has high thermal conductivity, low friction coefficient and good chemical stability, which is beneficial to improving the thermal conductivity of the coating, enhancing lubricity and hardness, and extending the service life of the coating; adding silicate is beneficial to improving the water resistance and stability of the coating, and by adding a stabilizer, it is used to increase the stability of the coating and prevent the precipitation of gel after the complexing agent is placed for a certain period of time; by adding a hydrophobic agent, it is used to increase the hydrophobicity of the coating and maintain the adhesion of the coating.

[0016] The silicate is any two or more of potassium silicate, sodium silicate and aluminum silicate.

[0017] The stabilizer is a silicate stabilizer.

[0018] The water repellent is sodium methyl silicate.

[0019] A method for preparing a pure inorganic water-based zinc-aluminum coating comprises the following steps:

[0020] S1: Preparation of modified ultrafine flaky zinc-aluminum powder: Weigh flaky zinc-aluminum powder, titanium dioxide, fumed silicon dioxide and boron nitride and add them into a ball mill, and grind and mix them under nitrogen protection to ensure uniform dispersion, thereby obtaining modified ultrafine flaky zinc-aluminum powder;

[0021] S2: Preparation of modified inorganic salt complexing agent: weigh silicate and water repellent, put them into a normal pressure reaction synthesis device, compound them, add distilled water to dilute, add stabilizer to stir, stir evenly, cool, and then obtain modified inorganic salt complexing agent;

[0022] S3: Take 1 part by weight of the ultrafine flaky zinc-aluminum powder prepared from S1 and 2.4 parts by weight of the modified inorganic salt complex complexing agent prepared from S2, add 1 part of the ultrafine flaky zinc-aluminum powder and 0.8 parts of the modified inorganic salt complex complexing agent into a stirring container for the first stirring, then add 1.6 parts of the modified inorganic salt complex complexing agent into the stirring container in two portions for the second stirring, and the coating can be obtained.

[0023] Through the above scheme, the method is adopted to prepare the coating, the operation steps are simple, and the addition order of different raw materials, temperature and stirring conditions are reasonably arranged, so that the final coating has good high temperature resistance and wear resistance, and strong adhesion to metal workpieces. The coating does not emit volatile organic compounds during use, is safe and environmentally friendly, and avoids causing pollution to the environment.

[0024] The mixing time of the grinding and mixing in S1 is 90 to 120 minutes, and the mixing temperature is 50 to 60°C.

[0025] The compounding temperature in S2 is 70-80°C, and the stirring time is 40-90 min; the dilution temperature in S2 is 80°C, and the stirring time is 20-30 min; the stirring temperature in S2 is 80°C, and the stirring time is 30-40 min.

[0026] In S3, the first stirring time is 20 to 30 minutes, and the stirring speed is 30 to 50 r / min; the second stirring time is 60 to 90 minutes, and the stirring speed is 60 to 80 r / min.

[0027] First, remove the rust on the surface of the metal workpiece, then add the paint into the spray pot, start compressed air, and spray the paint on the surface of the metal workpiece. After an interval of 30 minutes, spray a second time, put the sprayed metal workpiece into an oven and bake it to get the coating.

[0028] Through the above scheme, the construction process of the coating is simple, and it can be used in combination with conventional oil-based coatings and water-based coatings. It can realize the coating of zinc-rich layers on the metal surfaces of equipment and structural parts used in large-scale engineering construction projects, thereby solving the problem of low corrosion resistance of workpieces or equipment.

[0029] The baking temperature is 125-135° C., and the baking time is 30 minutes.

[0030] The above solution has the following advantages:

[0031] By adopting the preparation method of the present invention, in the process of preparing the coating, the operation steps are simple, and the addition order of different raw materials, temperature, stirring and other conditions are reasonably arranged, so that the coating finally obtained has good high temperature resistance and wear resistance, and has strong adhesion to metal workpieces. The coating has no volatile organic compound emissions during use, is safe and environmentally friendly, and the addition of flaky zinc-aluminum powder is used to improve the anti-corrosion performance of the coating, thereby enhancing the safety of the enterprise's anti-corrosion construction. The coating has a simple construction process and can be used in combination with conventional oil-based coatings and water-based coatings. DETAILED DESCRIPTION

[0032] The following will be combined with the specific embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] The embodiments of the present application are a pure inorganic water-based zinc-aluminum coating, a preparation method and an application thereof.

[0034] The silicate stabilizer used in Examples 1 to 3 and Comparative Examples 1 to 2 is of model GSYWDJ-5.

[0035] Step 1: Prepare raw materials of different weights

[0036] Example 1: A pure inorganic water-based zinc-aluminum coating, composed of the following raw materials in parts by weight:

[0037] The modified ultrafine flaky zinc-aluminum powder includes the following raw materials in parts by weight:

[0038] The weight portion of the flaky zinc-aluminum powder is 25 parts, the weight portion of titanium dioxide is 0.5 parts, the weight portion of fumed silicon dioxide is 0.1 parts, and the weight portion of boron nitride is 0.1 parts;

[0039] The modified inorganic salt complexing agent includes the following raw materials in parts by weight:

[0040] The weight parts of potassium silicate and sodium silicate are 40 parts, the weight part of silicate stabilizer is 20 parts, the weight part of sodium methyl silicate is 0.1 part, and the weight part of distilled water is 0.1 part.

[0041] Example 2: A pure inorganic water-based zinc-aluminum coating, composed of the following raw materials in parts by weight:

[0042] The modified ultrafine flaky zinc-aluminum powder includes the following raw materials in parts by weight:

[0043] The weight portion of the flaky zinc-aluminum powder is 30 parts, the weight portion of titanium dioxide is 1 part, the weight portion of fumed silicon dioxide is 0.3 parts, and the weight portion of boron nitride is 0.3 parts;

[0044] The modified inorganic salt complexing agent includes the following raw materials in parts by weight:

[0045] The weight proportions of sodium silicate and aluminum silicate are 45 parts, the weight proportion of silicate stabilizer is 25 parts, the weight proportion of sodium methyl silicate is 0.5 parts, and the weight proportion of distilled water is 0.5 parts.

[0046] Example 3: A pure inorganic water-based zinc-aluminum coating, composed of the following raw materials in parts by weight:

[0047] The modified ultrafine flaky zinc-aluminum powder includes the following raw materials in parts by weight:

[0048] The weight proportion of the flaky zinc-aluminum powder is 35 parts, the weight proportion of titanium dioxide is 2 parts, the weight proportion of fumed silicon dioxide is 0.5 parts, and the weight proportion of boron nitride is 0.5 parts;

[0049] The modified inorganic salt complexing agent includes the following raw materials in parts by weight:

[0050] The weight parts of potassium silicate and aluminum silicate are 50 parts, the weight part of silicate stabilizer is 30 parts, the weight part of sodium methyl silicate is 1 part, and the weight part of distilled water is 1 part.

[0051] Comparative Example 1: A pure inorganic water-based zinc-aluminum coating, composed of the following raw materials in parts by weight:

[0052] The modified ultrafine flaky zinc-aluminum powder includes the following raw materials in parts by weight:

[0053] The weight portion of the flaky zinc-aluminum powder is 20 parts, the weight portion of titanium dioxide is 0.2 parts, the weight portion of fumed silicon dioxide is 0.05 parts, and the weight portion of boron nitride is 0.05 parts;

[0054] The modified inorganic salt complexing agent includes the following raw materials in parts by weight:

[0055] The weight proportions of sodium silicate and aluminum silicate are 20 parts, the weight proportion of silicate stabilizer is 10 parts, the weight proportion of sodium methyl silicate is 0.05 parts, and the weight proportion of distilled water is 0.05 parts.

[0056] Comparative Example 2: A pure inorganic water-based zinc-aluminum coating, composed of the following raw materials in parts by weight:

[0057] The modified ultrafine flaky zinc-aluminum powder includes the following raw materials in parts by weight:

[0058] The weight proportion of the flaky zinc-aluminum powder is 40 parts, the weight proportion of titanium dioxide is 3 parts, the weight proportion of fumed silicon dioxide is 1 part, and the weight proportion of boron nitride is 1 part;

[0059] The modified inorganic salt complexing agent includes the following raw materials in parts by weight:

[0060] The weight parts of sodium silicate and aluminum silicate are 60 parts, the weight part of silicate stabilizer is 40 parts, the weight part of sodium methyl silicate is 2 parts, and the weight part of distilled water is 2 parts.

[0061] Step 2: A method for preparing a pure inorganic water-based zinc-aluminum coating, comprising the following steps:

[0062] S1. Prepare materials: weigh all raw materials according to the above formula ratio and set aside;

[0063] S2, first add flaky zinc-aluminum powder, titanium dioxide, fumed silicon dioxide and boron nitride into a ball mill, use nitrogen protection, grind and mix, grind for 90 to 120 minutes, the mixing temperature is 50 to 60 ° C, ensure uniform dispersion, and obtain modified ultrafine flaky zinc-aluminum powder;

[0064] S3, put the silicate and the water repellent into a normal pressure reaction synthesis device, heat to 70-80°C, stir for 40-90min, compound, add distilled water for dilution, keep the temperature at 80°C, stir for 20-30min, then add the stabilizer and stir, keep the temperature at 80°C, stir for 30-40min, stir evenly, and cool to obtain a modified inorganic salt complexing agent;

[0065] S4. Take 1 part by weight of the ultrafine flaky zinc-aluminum powder prepared from S1 and 2.4 parts by weight of the modified inorganic salt complex complexing agent prepared from S2. First add 1 part of the ultrafine flaky zinc-aluminum powder and 0.8 parts of the modified inorganic salt complex complexing agent into a stirring container, stir at a low speed for 20 to 30 minutes at a stirring speed of 30 to 50 r / min, then add 1.6 parts of the modified inorganic salt complex complexing agent into the stirring container in two portions and stir for the first time at a stirring time of 60 to 90 minutes at a stirring speed of 60 to 80 r / min to obtain the coating.

[0066] Step 3: Application of a pure inorganic water-based zinc-aluminum coating

[0067] First, remove the rust on the surface of the metal workpiece, then add the paint into the spray pot, start compressed air, and spray the paint on the surface of the metal workpiece. After an interval of 30 minutes, spray a second time, put the sprayed metal workpiece into an oven and bake it at 125-135°C for 30 minutes to obtain a coating with a thickness of 15-25μm, neutral salt spray resistance of more than 1000h, and high temperature resistance of up to 400°C.

[0068] Step 4: Experimental data

[0069]

[0070] Experimental conclusion:

[0071] The results show that the raw materials used in preparing the coatings in Examples 1 to 3 and Comparative Examples 1 to 2 are all inorganic materials, the production process, coating process and coating will not cause pollution to the environment, the VOC of the product is lower than 2PPM, and it can be widely used in metal corrosion protection in various fields; however, compared with Examples 1 to 3, there are significant differences in the thickness and neutral salt spray of the coatings in Comparative Examples 1 to 2; the coating thickness, neutral salt spray and high temperature resistance of Examples 1 to 3 are all high, and the cost performance is high. From the experimental data, Example 2 has the best data, and the coating thickness, neutral salt spray and high temperature resistance are all better.

[0072] Compared with the electro-galvanized coating, the coating of Example 2 is much thinner than that of Example 2. The emissions of volatile organic compounds from the electro-galvanized coating, hot-dip galvanized coating and Dacromet coating are all higher than that of Example 2. The electro-galvanized coating, hot-dip galvanized coating, Dacromet coating and Dacromet coating have poor water-based environmental protection and average cost-effectiveness.

[0073] The coating formed by paint application is an inorganic coating, which can withstand high temperatures of over 400°C for long-term use, and its high temperature resistance is much greater than that of conventional organic coatings. After the coating is kept at 400°C in a high-temperature furnace for 1 hour, the color of the paint film does not change, the surface is intact, and there are no bubbles or cracks.

[0074] The coating thickness is 15-25μm, the coating area per unit weight is large, the cost performance is high, the salt spray resistance time in the neutral salt spray test is greater than 1000 hours, and the corrosion resistance is much greater than that of epoxy zinc-rich coating.

[0075] The raw materials required for the production of this coating are all conventional raw materials and are easily available on the market. Compared with coatings of the same purpose, the coating produced by this invention is more environmentally friendly, has good high temperature resistance and wear resistance, can be widely used in metal corrosion protection in various fields, and has superior cost and performance advantages.

Claims

1. A pure inorganic water-based zinc-aluminum coating, characterized in that: Including modified ultra-fine flaky zinc-aluminum powder and modified inorganic salt complexing agent, The modified ultrafine flaky zinc-aluminum powder includes the following raw materials in parts by weight: The weight proportion of the flaky zinc-aluminum powder is 25 to 35 parts, the weight proportion of titanium dioxide is 0.5 to 2 parts, the weight proportion of fumed silicon dioxide is 0.1 to 0.5 parts, and the weight proportion of boron nitride is 0.1 to 0.5 parts; The modified inorganic salt complexing agent includes the following raw materials in parts by weight: The weight proportion of the silicate is 40-50 parts, the weight proportion of the stabilizer is 20-30 parts, the weight proportion of the hydrophobic agent is 0.1-1 part, and the weight proportion of the distilled water is 0.1-1 part.

2. A pure inorganic water-based zinc-aluminum coating as claimed in claim 1, characterized in that: The silicate is any two or more of potassium silicate, sodium silicate and aluminum silicate.

3. A pure inorganic water-based zinc-aluminum coating as claimed in claim 1, characterized in that: The stabilizer is a silicate stabilizer.

4. A pure inorganic water-based zinc-aluminum coating as claimed in claim 1, characterized in that: The water repellent is sodium methyl silicate.

5. The method for preparing a pure inorganic water-based zinc-aluminum coating according to claim 1, characterized in that: The following steps are involved: S1: Preparation of modified ultrafine flaky zinc-aluminum powder: Weigh flaky zinc-aluminum powder, titanium dioxide, fumed silicon dioxide and boron nitride and add them into a ball mill, and grind and mix them under nitrogen protection to ensure uniform dispersion, thereby obtaining modified ultrafine flaky zinc-aluminum powder; S2: Preparation of modified inorganic salt complexing agent: weigh silicate and water repellent, put them into a normal pressure reaction synthesis device, compound them, add distilled water to dilute, add stabilizer to stir, stir evenly, cool, and then obtain modified inorganic salt complexing agent; S3: Take 1 part by weight of the ultrafine flaky zinc-aluminum powder prepared from S1 and 2.4 parts by weight of the modified inorganic salt complex complexing agent prepared from S2, add 1 part of the ultrafine flaky zinc-aluminum powder and 0.8 parts of the modified inorganic salt complex complexing agent into a stirring container for the first stirring, then add 1.6 parts of the modified inorganic salt complex complexing agent into the stirring container in two portions for the second stirring, and the coating can be obtained.

6. A method for preparing a pure inorganic water-based zinc-aluminum coating as claimed in claim 5, characterized in that: The mixing time of the grinding and mixing in S1 is 90 to 120 minutes, and the mixing temperature is 50 to 60°C.

7. The method for preparing a pure inorganic water-based zinc-aluminum coating as claimed in claim 5, characterized in that: The compounding temperature in S2 is 70-80°C, and the stirring time is 40-90 min; the dilution temperature in S2 is 80°C, and the stirring time is 20-30 min; the stirring temperature in S2 is 80°C, and the stirring time is 30-40 min.

8. The method for preparing a pure inorganic water-based zinc-aluminum coating according to claim 5, characterized in that: In S3, the first stirring time is 20 to 30 minutes, and the stirring speed is 30 to 50 r / min; the second stirring time is 60 to 90 minutes, and the stirring speed is 60 to 80 r / min.

9. An application of a pure inorganic water-based zinc-aluminum coating, characterized in that: First, remove the rust on the surface of the metal workpiece, then add the paint into the spray pot, start compressed air, and spray the paint on the surface of the metal workpiece. After an interval of 30 minutes, spray a second time, put the sprayed metal workpiece into an oven and bake it to get the coating.

10. The use of a pure inorganic water-based zinc-aluminum coating as claimed in claim 9, characterized in that: The baking temperature is 125-135° C., and the baking time is 30 minutes.

Citation Information

Patent Citations

  • Waterborne inorganic zinc-rich coating capable of realizing long-term corrosion protection based on single coating layer

    CN106883645A

  • Waterproof metal paint for shell of filter and preparation method of waterproof metal paint

    CN107325731A

  • Inorganic silicate coating and preparation method thereof

    CN113214689A

  • Fireproof high-temperature-resistant heavy-duty anticorrosive coating and preparation method thereof

    CN115785716A

  • Aqueous inorganic silicate zinc-rich primer

    CN1840586A